Transient stability of a single machine connected to an infinite bus / Tengku Mohamad Razreen Che Rashdi - Che Rashdi, Tengku Mohamad Razreen (2012)
Transient stability studies are aimed at determining whether a system will remain synchronizes subsequent major disturbances such as three phase fault. Due to this, transient stability analysis is development for this project so it can determine the stability condition of power system network when disturbance occurs'. The objective of this study is to understand the transient behavior of synchronous generator and method of improving its transient stability. This paper analyzed the transient stability of a power system comprising of a single generator that is connected to infinite bus. The type of fault that was introduced to the system is the three phase fault since this is the most severe type of fault encountered. The result of terminal voltage, load angle, rotor speed and the active and reactive power supplied to the grid is measured using the oscilloscopes. A comparison between the condition with and without three phase short circuit will be obtained using Matlab. Three methods are being analyzed to determine which method is the best to improve the transient stability of synchronous machine. First is to add an excitation system to the circuit. It will then be added with an additional power system stabilizer to the circuit that has excitation system installed. Finally, it will be combined with the turbine-governor control. Based on the result from the simulation, it is proven that the last method is the best method for improving stability.